The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s42765-020-00030-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Annealing on Mid-Infrared Transmission in Semiconductor Alloy-Core Glass-Cladded Fibers

Abstract: We report a study investigating the effects of thermal annealing on the optical properties of Si-Ge alloy-core silica-cladded fibers. Low temperature fiber draw was performed with a laboratory-made draw tower at 1760 °C that minimizes impurity diffusion from cladding to the core. As a post-drawing process, Si-Ge core fibers were annealed in a box furnace to alter the core structure. Microstructural and optical properties of fibers were investigated, and transmission losses were measured as 28 dB/cm at 6.1 µm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Methods that have been used to perform post-fabrication annealing/recrystallisation of continuous crystalline core fibres include oven thermal annealing 72 , rapid photothermal annealing 73 , laser treatment (at both visible 74 and IR 46 , 47 wavelengths) and diverse heating methods in tapering rigs. The non-standard treatments are illustrated in Fig.…”
Section: Semiconductor Core Fibresmentioning
confidence: 99%
See 2 more Smart Citations
“…Methods that have been used to perform post-fabrication annealing/recrystallisation of continuous crystalline core fibres include oven thermal annealing 72 , rapid photothermal annealing 73 , laser treatment (at both visible 74 and IR 46 , 47 wavelengths) and diverse heating methods in tapering rigs. The non-standard treatments are illustrated in Fig.…”
Section: Semiconductor Core Fibresmentioning
confidence: 99%
“…4 , fibres typically are drawn at temperatures of ~1950 °C, based on the use of silica as the cladding. SiGe based fibres with Ge concentrations from 1 at% 99 to 46 at% 118 have been studied, both as continuous fibre cores 46 , 72 , 75 , 118 , and as source material for particles 48 within the silica cladding. Compositional variations due to the preferential solidification of silicon from the melt are observed in the as-drawn material 75 , 118 , as seen in Fig.…”
Section: Materials and Phase Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compositional variations along the fiber's length is a potential route for the fabricating in-fiber diode-like structure, leading to photodetection and solar cell applications, while the radial graded core structure is particular useful for infrared transmission beyond 4 µm as the Gerich region serves as the preferential guiding medium. Numerical studies suggested a graded-index core structure could have a 100-time lower transmission loss in the mid-IR region and also suppress the strong absorption by the silica cladding [84].…”
Section: Semiconductor Alloysmentioning
confidence: 99%
“…If the speed exceeds a critical value, non-planar growth results. For a radially dominated cooling process, a high transverse scan speed can lead to the formation of a concave crystallization front in a cylindrical geometry [33,34] and the large surface-to-volume ratio of a fiber may be expected to enhance this effect. BSE images in Fig.…”
Section: Laser Scan Speedmentioning
confidence: 99%